2021
DOI: 10.1038/s41598-021-91506-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis on the adjunctive use of host immune modulators in non-surgical periodontal treatment in healthy and systemically compromised patients

Abstract: Considering the central role of inflammation in the pathogenesis of periodontitis, the combination of NSPT with different agents that can modulate the host immune-inflammatory response has been proposed to enhance the outcomes of NSPT. The aim of this paper is to systematically review the literature on the efficacy of systemic host modulators (HMs) as adjuncts to non-surgical periodontal therapy (NSPT) in improving pocket depth (PD) reduction and clinical attachment level (CAL) gain in healthy and systemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 70 publications
(149 reference statements)
2
15
0
Order By: Relevance
“…NSPT has been proved to improve the level of clinical attachment and effectively reduce the probing pocket depth [ 22 , 23 ]. Therapy includes oral hygiene instruction, subgingival scaling, and root planing [ 5 ]. Gingival bleeding is the most common complication after supra- and subgingival curettage and the most common symptom in periodontal emergency departments [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSPT has been proved to improve the level of clinical attachment and effectively reduce the probing pocket depth [ 22 , 23 ]. Therapy includes oral hygiene instruction, subgingival scaling, and root planing [ 5 ]. Gingival bleeding is the most common complication after supra- and subgingival curettage and the most common symptom in periodontal emergency departments [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the periodontitis therapy is to address gingival inflammation and restore periodontal health. Periodontal therapy always begins with nonsurgical periodontal therapy (NSPT) [ 5 ]. NSPT is engaged to preserve, improve, and maintain natural dentition [ 6 ], including by controlling (reducing/eliminating) the subgingival biofilm and calculus through manual subgingival instrumentation and follow-up in all periodontitis patients, irrespective of the disease stage, for all teeth with loss of periodontal support and/or periodontal pocket formation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the majority of included studies aggregated patient‐level data providing mean full‐mouth clinical periodontal measurements. Although this allows to assess an overall effect of the different adjunctive therapies on the periodontal condition of the patient, it should be recognized that periodontitis is most often a site‐specific disease, and by aggregating patient‐level evaluations there is the risk of losing important information and diluting the real effect that these therapies might have had 14 . It is, therefore, recommended that future studies should perform multilevel analyses to assess not only patient‐level but also site‐level responses to adjunctive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…While it appears that most probably adjunctive therapies should not be used routinely as an adjunct to subgingival instrumentation, some recent studies have suggested that they might be particularly beneficial in specific cases, which might include sites that did not adequately respond to the initial nonsurgical therapy, or they might provide additional benefits in specific categories of patients, such as patients affected by systemic diseases (e.g. diabetes mellitus) with an inflammatory pathogenesis 14,15 . For instance, although systemic probiotics did not show to significantly improve the outcomes of subgingival instrumentation in previously untreated periodontitis patients, 15 two recent RCTs suggested a significant improvement in pocket reduction when used as an adjunctive treatment in patients with residual pockets 16,17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation